This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: Fu (a,b) = grad f(a,b)*ugrad f(a,b)*u =fx(a,b)*u1+fy(a,b)*u2 U = 1/(SQ(2))*(i+j), .f(x,y) = x^2+y^2 and fu (1,0) Use grad f(x,y) =2xi +2yj. .grad f(1,0) = 2i Fu(1,0) = 2i*u ===2*1/((SQ(2))===SQRT(2) Find grad.z = (x+y)e^y.Zx=e^yand Zy = xe^y+e^y+ye^y SO Z = Zxi+ZyjZ = e^yi+(xe^y+e^y+ye^y)...
View Full Document
This note was uploaded on 03/21/2011 for the course MTH 243 taught by Professor Barabara during the Spring '11 term at Rhode Island.
- Spring '11